THE DEVELOPMENT OF NATURAL SYMPTOMS BOOK (GELAM) AS A PRAYER LEARNING ON THE SUB THEME OF NATURAL SYMPTOMS FOR CHILDREN AGED 5-6 YEARS - Yuli Tri Andini; Moh. Anas Syamsudin (International Conference on Humanity Education and Society (ICHES), 2023)
The objects of this study are teachers and children who have an age range of 5-6 years. This study aims to develop teaching materials in the form of books that discuss prayer when natural symptoms occur in the child's environment. Natural symptoms are one of the events that are close to the child. This can be seen from the geographical location and tropical climate of Indonesia which allows natural symptoms to be often encountered. However, the introduction and discussion of prayer when natural symptoms occur that the teacher gives to the child is still limited. The method used in this study is the Borg & Gall Research and Development (RnD) method. This book was created using the Maeromedia Flash 8 e-software and Photoshop Cs6. Trials were carried out in 2 stages, namely small-scale trials and field trials. A small-scale trial involved 20 children taken from 1 kindergarten. A field trial involved 50 children drawn from 3 kindergartens. The results of this study show a validity value above 0.6 which means that the teaching material development book is valid, so it can be concluded that this teaching material development book is suitable for use for children aged 5-6 years